Association Between Serum Uric Acid and Prediabetes in the Korean General Population. (November 2019) - Park, Ryoung Jin; Kang, Min Gu
The purpose of this study is to examine the relation of serum uric acid with prediabetes in Korea. We conducted a cross-sectional study in 4633 individuals aged 20 to 81 years who participated in the 2016 Korean National Health and Nutrition Examination Survey. Participants are considered to have prediabetes if they have one or more of the following: impaired fasting glucose (fasting blood glucose levels between 5.6 and 6.9 mmol/L); impaired hemoglobin A1c (hemoglobin A1c ranges of 5.7% to 6.4% [39-46 mmol/mol]). Multiple logistic regression analysis was used to compute odds ratios (ORs) and 95% confidence intervals (CIs). Prediabetes was more prevalent in the hyperuricemia group compared with the normal-range group among men (OR = 1.51; 95% CI = 1.11-2.05; P < .01) and women (OR = 1.84; 95% CI = 1.01-3.37; P = .04) after adjustment for age, body mass index, abdominal obesity, blood pressure, triglyceride, high-density lipoprotein cholesterol, renal function, alcohol consumption, smoking, and physical activity level. For a standard deviation increment in uric acid, the odds of having prediabetes as compared with that of not having prediabetes increased about 114% in men ( P = .05) and 116% in women ( P = .01). Higher levels of uric acid were associated with an increased risk of prediabetes among the general Korean population.